A single dose of intravenous combretastatin A4‐phosphate is reasonably well tolerated and significantly reduces tumour vascularization in canine spontaneous cancers. (24th May 2018) - Abma, E.; De Spiegelaere, W.; Vanderperren, K.; Stock, E.; Van Brantegem, L.; Cornelis, I.; Daminet, S.; Ni, Y.; Vynck, M.; Verstraete, G.; Smets, P.; de Rooster, H.
Abstract : Combretastatin A4‐phosphate (CA4P) is an anti‐tumour vascular targeting agent which selectively blocks tumour blood flow. Research on CA4P in rodent tumour models is extensive; however, knowledge of its effect on spontaneous cancer is scarce. This study was conducted in canine patients with spontaneous solid tumours. The goal was to assess the toxicity and efficacy of CA4P in various spontaneous tumour types. Eight dogs with spontaneous tumours were enrolled and treated with a single dose of 75 mg m −2 intravenous CA4P. The dogs were screened and monitored before and after injection. Pre‐ and post‐treatment tumour blood flow was analysed in vivo by power Doppler ultrasound (PDUS) and contrast‐enhanced ultrasound (CEUS). Vessel destruction and tumour necrosis were evaluated by histopathology. Clinically relevant toxicity was limited to one case of temporary tetraparesis; other adverse events were mild. Significant cardiovascular changes were mostly confined to changes in heart rate and cTnI levels. Macroscopic tumour size reduction was evident in 2 dogs. Based on PDUS and CEUS, CA4P induced a significant decrease in vascular index and tumour blood flow. Post‐treatment, histopathology revealed a significant increase of necrotic tumoural tissue and a significant reduction in microvessel density in tumoural tissue. Anti‐vascular and necrotizing effects of CA4P were documented in a variety of canine spontaneous cancers with only minimal side effects. This is the first study reporting the administration of CA4P to canine cancer patients with in vivo and ex vivo assessment, and a first step toward implementing CA4P in combination therapies in veterinary oncology patients. The use of CA4P in canine patients was approved and registered by the Belgian Federal Agency for Medicines and Health Products (FAMHP) (approval number 0002588, registration number 6518 ID 2F12).